1986
DOI: 10.1136/thx.41.11.890
|View full text |Cite
|
Sign up to set email alerts
|

Aortic aneurysm caused by schistosomiasis.

Abstract: There has not been a previous report of schistosomiasis pro The haemoglobin concentration was 9 7 g/dl, and the white blood cell count 16 x 109/l with an eosinophilia of 10%. There was blood in the urine but no ova of Schistosoma were identified. Stools showed the ova of S mansoni, as did a biopsy specimen of the rectal mucosa. Serological tests for syphilis (Venereal Disease Research Laboratory, Wassermann reaction) were negative. The results of liver function tests, including the prothrombin index, were norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In this respect, obliterative endarteritis in the vasa vasorum of the large pulmonary arteries in cases of pulmonary schistosomiasis has been reported to weaken their walls, leading to dilatation even in the absence of pulmonary hypertension [8]. Interestingly, the same mechanism was specified in the first reported case of schistosomal aortic aneurysm, where an extensive infestation of the left upper lobe by ova of Schistosoma mansoni caused extension of the disease into the adjacent pleura and aortic sheath, producing endarteritis obliterans of the vasa vasorum of the aorta and subsequent formation of an aortic aneurysm in the absence of systemic hypertension [12]. …”
Section: Discussionmentioning
confidence: 91%
“…In this respect, obliterative endarteritis in the vasa vasorum of the large pulmonary arteries in cases of pulmonary schistosomiasis has been reported to weaken their walls, leading to dilatation even in the absence of pulmonary hypertension [8]. Interestingly, the same mechanism was specified in the first reported case of schistosomal aortic aneurysm, where an extensive infestation of the left upper lobe by ova of Schistosoma mansoni caused extension of the disease into the adjacent pleura and aortic sheath, producing endarteritis obliterans of the vasa vasorum of the aorta and subsequent formation of an aortic aneurysm in the absence of systemic hypertension [12]. …”
Section: Discussionmentioning
confidence: 91%
“…In some cases, they occurred in patients with active Schistosoma infection. In these cases, the diagnosis of Schistosoma infection was reached by serological investigations [ 22 ], stool sample assessment, rectal biopsy [ 19 ], and histology of lung [ 17 ] or of liver and testis [ 23 ].…”
Section: Investigation Outcomesmentioning
confidence: 99%
“…When we analysed the age at which patients were diagnosed with an aneurysm, we observed that young patients can be affected. The youngest patient included in our review was 18-years old, and overall, five patients were below 40 years [ 13 , 18 , 19 , 22 , 27 ]. This differs from the usual age at diagnosis of atherosclerotic aneurysms and suggests the need for an increased clinical suspicion of aneurysm as differential diagnosis when assessing patients of young age with compatible clinical presentation in endemic areas (Tables 3 and 4 ).…”
Section: Investigation Outcomesmentioning
confidence: 99%
See 2 more Smart Citations